ANALYSIS ON THE VALUE RELEVANCE OF CASH OPERATING PROFIT AND BOOK VALUE OF EQUITY SHARES AT THE PRICE IN STOCK suspension LISTED COMPANIES IN THE INDEX IN BEI LQ45 - Taufik, Muhammad; one, Dr.Prihantoro (Accounting, 2009)
So far the study of the relevance of earnings, cash flow value, and the book reveals that the value of earnings and book value are positively correlated to the stock price while cash flow has no information content if the visible effects on stock prices. This study aimed to determine the influence of the value relevance of earnings, operating cash flow and book value of equity to the stock price. This study uses data of registered companies in LQ45 as of August 2008 until January 2009. Data analysis was done through multiple regression, where prior to regression analysis of data was tested first with the classic assumption test. Data analysis showed that the influence of the value relevance of earnings, operating cash flow and book value of shares in the period hargpa non suspension of shares indicate that the value relevance of earnings and book value significantly influence stock prices, while operating cash flow variable has no significant effect. Meanwhile, the value relevance test the influence of profit, operating cash flow and book value to share price on stock suspension period indicates that the variable income is a variable one - the only significant effect on stock prices, while the cash flow variable is a variable that has a negative and not significant. While the book value variable is a variable with a positive but not significant effect. Keywords : profit, book value, equity shares